THE PIBID AND OBJECTIVES CONSIDERED IN EDUCATION IN PHYSICAL SUBPROJECT GOIANIA-GO (Fiep Bulletin - online, 2017)
The construction of this text was given from the development of the activities planned in the first year ofparticipation of Physical Education in PIBID a higher education institution in Goiânia-GO. The aim was to use this research as aform of dialogue which portray important aspects involved in the design of PIBID. an assessment and analysis of the resultsobtained in 2014 using the answers to a questionnaire of closed and open questions applied to 15 fellows and three members ofthe supervisory subproject was made. The results observed in the ratings denote the scope of the main preset targets for theannual plan of the area subproject.